Supporting Women Entrepreneurs in Uzbek Economy - Nazarova, Kamila; Khabibiy, Nigina (MMIT Proceedings, 2024)
Like all Soviet Central Asian republics, Uzbekistan underwent great political, economic, and social transformations following its independence in 1991. Economic crises touched most of the local economies. As a result, millions of Uzbeks, Kyrgyz, and Tajiks went to Russia to find jobs and even the current economic crisis in Russia did not stop migrants from leaving the region to work in Russia, accelerating the globalization of Central Asian societies. Globalization has been changing and influencing cultures, traditional structures, social norms, and beliefs all over the world. The accelerated speed of shared information, objects, ideas, and humans has led to increased mobility and significant change in each corner of the world today. Uzbekistan was also affected by these processes of globalization, mobility, and change, opening up new opportunities for the population (Turaeva, 2017). Successful entrepreneurs are supposed to create jobs, pay taxes, offer new ideas, and contribute to long-term economic progress. Increased competition from entrepreneurs’ forces established businesses to become more competitive. Entrepreneurs provide new job possibilities and speed structural change by displacing old, sluggish businesses. However, women continue to be underrepresented in the ranks of entrepreneurs, particularly in transitional countries. Women own and manage significantly fewer enterprises than males around the world, and they earn less on average and are more likely to work in unprotected jobs, such as domestic work. Despite a rising literature, more research on female entrepreneurship is needed, hence we focus on Uzbekistan, a middle-income transition country with an increasing number of initiatives targeted at supporting and empowering female entrepreneurs (Mirkasimov, 2017).